Geographies of Fashion and Style: Setting the Scene. Issue 1 (1st June 2021) - Patchett, Merle; Williams, Nina
Abstract : The papers assembled in this forum examine the Geographies of Fashion and Style through texts, visual images, material objects and processes of growing and making, as lived experiences and performative practices and, crucially, as concepts and practices that travel and mutate over time and place. In this introduction, we chart the Eurocentric cultural episteme of the fashion industry and fashion studies and dismantle it by drawing on, and out, globally-orientated and decentered approaches to the study of fashion and style. Our contribution to debates on fashion and style is to draw out five impulses arising at the intersections of geography and fashion studies and which our collection of papers brings to the fore: Theorizing, Queering, Decolonizing, Ecologizing, and Curating. In doing so, our introduction foregrounds the significance of fashion and style as sites of (micro) political problems and potentials, and is a call and a framework through which to extend and take seriously the diverse processes of fashion and style as sentient to the broader themes and scholarship of concern in the geohumanities.